PENINGKATAN HASIL BELAJAR AGAMA BUDDHA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN YOUTUBE - Sutopo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
Technology develops so rapidly that all human needs in all fields experience a drastic change from delay to acceleration, from backwardness to progress, and from closed nature to open nature. Learning media is one of the important elements in the learning process. One form of learning media used in technological development is Youtube. This research was Classroom Action Research (CAR). The design in this research was a model of Kemmis and Mc. Taggart in form of a spiral from one cycle to the next cycle. Each cycle included planning, action, observation, and reflection. This research was conducted at SMA Negeri 1 Bengkalis. The subjects of this study were Buddhist students at grade X (Ten) Social Studies of SMA Negeri 1 Bengkalis, for as many as 24 students. Learning in two cycles showed an increase in students’ learning outcomes. In the first cycle, the average score was <75 (75%), while in the second cycle, the average score was >75 (75%). Thus, utilizing youtube increased students' attractiveness to learning and improved students’ learning outcomes.